Lattice effects on the magnetoresistance in doped LaMnO3. - Hwang, H; Cheong, S; Radaelli, P; Marezio, M; Batlogg, B (1995)
A detailed study of doped LaMnO3 with fixed carrier concentration reveals a direct relationship between the Curie temperature Tc and the average ionic radius of the La site rA, which is varied by substituting different rare earth ions for La. With decreasing rA, magnetic order and significant magnetoresistance occur at lower temperatures with increasing thermal hysteresis, and the magnitude of the magnetoresistance increases dramatically. These results show that the notion of "double exchange" must be generalized to include changes in the Mn-Mn electronic hopping parameter as a result of changes in the Mn-O-Mn bond angle. © 1995 The American Physical Society.